Análises genômicas da onça-pintada (Panthera onca) : caracterização do genoma completo e investigação de regiões sob seleção através de comparações interespecíficas e populacionais - Figueiró, Henrique Vieira (2016)
In the past 10 years, high throughput sequencing has revolutionized evolutionary biology. With the technical advances that emerged with the genome sequencing of model species, it is now possible to apply these techniques to taxonomic groups without any previously available genetic resources. Complete genome sequencing and reduced representation methods have enabled us to explore deeper evolutionary questions, such as detecting ancient hybridization and signatures of selection on a genomic scale. Among the groups that could benefit from these methods is the Panthera genus. The group is composed by five species (P. onca, P. tigris, P. leo, P. pardus and P. uncia), all of which are large felids that exert important ecological role as apex predators in their habitats. Their low densities, alarming rates of habitat loss and chronic conflict with humans, all of them are threatened with extinction in the wild and thus important targets for conservation. One of the species in this group, the jaguar (P. onca), is the only member of the genus currently present in the Neotropical region, and the focus of our study. The jaguar has a color pattern similar to that of the leopard, but a much more robust constitution, with massive jaws and shorter limbs. The present study aims to characterize for the first time the jaguar genome, and to perform comparative analyses with the genomes from all other Panthera species. In addition, we seek to perform population genomic analyses with Brazilian jaguar populations and search for signatures of divergent selection in different regions. We have sequenced four genomic libraries, with an estimated coverage depth of 84x. The complete genome sequence allowed the annotation of 25,441 genes and the description of other genomic features (e.g. ncRNA, microsatellites, numts). Additionally, we have sequenced the genome of a leopard at low coverage, with an estimated depth of 25x. With the addition of these two genomes, we were able obtain a genomic data set containing all five Panthera species, which was used to perform phylogenetic discordance analyses and to detect signatures of selection using a dataset encompassing 13,143 orthologous genes. We were able to demonstrate the presence of hybridization events during the speciation process of the species, as well as signatures of selection in genes potentially involved in important characteristics of these iconic animals. Among them, the jaguar’s robust build, the social behavior of lions, cold environment adaptations in the snow leopard and the tiger’s stripes. Using an exome capture approach, we performed a population genomics study targeting jaguar populations from different Brazilian biomes. In addition to assessments of genetic diversity and population structure, we detected signals of local adaptation using multiple methods. Among the obtained results is the presence of genes under selection that are related to energetic metabolism in the Amazon, body development in the Pantanal and immunity in the Atlantic Forest. Additionally, we observed several pigmentation-related genes under selection in different biomes. Those genes affect not only pigmentation, but also have pleiotropic effects in development and immunity routes. Overall, these results help to understand the evolutionary processes that have shaped the adaptation of Panthera species, and particularly the jaguar, to the environments where they currently live.